How low is safe? The frontier of very low (<30 mg/dL) LDL cholesterol. (19th January 2021) - Karagiannis, Angelos D; Mehta, Anurag; Dhindsa, Devinder S; Virani, Salim S; Orringer, Carl E; Blumenthal, Roger S; Stone, Neil J; Sperling, Laurence S
Abstract: Low-density lipoprotein cholesterol (LDL-C) is a proven causative factor for developing atherosclerotic cardiovascular disease. Individuals with genetic conditions associated with lifelong very low LDL-C levels can be healthy. We now possess the pharmacological armamentarium (statins, ezetimibe, PCSK9 inhibitors) to reduce LDL-C to an unprecedented extent. Increasing numbers of patients are expected to achieve very low (<30 mg/dL) LDL-C. Cardiovascular event reduction increases log linearly in association with lowering LDL-C, without reaching any clear plateau even when very low LDL-C levels are achieved. It is still controversial whether lower LDL-C levels are associated with significant clinical adverse effects (e.g. new-onset diabetes mellitus or possibly haemorrhagic stroke) and long-term data are needed to address safety concerns. This review presents the familial conditions characterized by very low LDL-C, analyses trials with lipid-lowering agents where patients attained very low LDL-C, and summarizes the benefits and potential adverse effects associated with achieving very low LDL-C. Given the potential for cardiovascular benefit and short-term safe profile of very low LDL-C, it may be advantageous to attain such low levels in specific high-risk populations. Further studies are needed to compare the net clinical benefit of non-LDL-C-lowering interventions with very low LDL-C approaches, in addition to comparing the efficacy and safety of very low LDL-C levels vs. current recommended targets. Graphical Abstract: